Network pharmacology-driven investigation of luteolin from Annona muricata as a promising multi-target inhibitor for pancreatic cancer - Shalini Mathpal; P. Priyamvada; Gayathri Ashok; Tushar Joshi; Deepanjan Saha; Ankit Mukherjee; Biraj Roy; Sudha Ramaiah; Anand Anbarasu (Results in Chemistry)
Pancreatic cancer is a complex and heterogeneous malignancy ranking among the deadliest cancers. The late-stage diagnosis often limits treatment options and reduces survival rates. In recent years, Annona muricata (A. muricata) has emerged as a promising source of natural compounds exhibiting potential anticancer activity. This study utilizes an integrative network pharmacology approach to uncover the molecular mechanisms responsible for the therapeutic efficacy of A. muricata in Pancreatic cancer treatment. A total of 139 phytochemicals from A. muricata were screened for drug-likeness and pharmacokinetic (ADMET) properties, leading to the selection of 15 compounds with optimal profiles. Potential compound-related targets were identified using SwissTargetPrediction, while Pancreatic cancer-associated genes were retrieved from the DisGeNET database (DSI > 0.6). The interactome was generated by constructing a protein-protein interaction (PPI) network utilizing the STRING database and analyzed in Cytoscape, revealing four key hub genes: AKT1, EGFR, MMP9, and SRC. Molecular docking studies identified luteolin and kaempferol as the most effective compounds, exhibiting strong binding affinities across the hub targets, with luteolin demonstrating the lowest binding energies. These findings were further validated through 500 ns molecular dynamics (MD) simulations (in triplicate) confirmed the stability and compactness of the luteolin-target complexes. MM-PBSA binding free energy calculations supported these interactions, with favorable ΔG values of −27.35kcal/mol, −25.04kcal/mol, −32.89kcal/mol, and −29.12kcal/mol for AKT1, EGFR, MMP9, and SRC, respectively. This study highlights the multi-target potential of A. muricata phytochemicals, particularly luteolin, in inhibiting key signaling pathways of pancreatic cancer progression, paving the way for experimental validation and phytochemical-based therapies.